Autophagy-Mediated Synaptic Refinement and Auditory Neural Pruning Contribute to Ribbon Synaptic Maturity in the Developing Cochlea - Guo, Rui; Xu, Yice; Xiong, Wei; Wei, Wei; Qi, Yue; Du, Zhengde; Gong, Shusheng; Tao, Zezhang; Liu, Ke (Frontiers in Molecular Neuroscience, 2022)
In rodents, massive initial synapses are formed in the auditory peripheral nervous system in the early postnatal stage, and one of the major phenomena is that the number of afferent synapses in the cochlea is significantly reduced in the duration of development. This raises the hypothesis that the number of cochlear ribbon synapses are dramatically with hearing development and maturation. In this study, several tracers identifying activities of autophagy were applied to estimate the level of autophagy activity in the process of ribbon synapse development in mice; further, changes in the synaptic number and spiral ganglion nerve (SGN) fibers were quantitatively measured. We found robust expression of LC3B and lysosomal-associated membrane protein 1 as well as LysoTracker in or near inner hair cells and cochlear ribbon synapses in the early stage of postnatal development. Moreover, we found a significant loss in the intensity of SGN fibers at ribbon synaptic development and hearing onset. Thus, this study demonstrates that ribbon synaptic refinement and SGN fibers pruning are closely associated with the morphological and functional maturation of ribbon synapses and that synaptic refinement and SGN fiber pruning are regulated by the robust activities of autophagy in the earlier stages of auditory development.